Bunch moth, Tirathaba rufivena (lepidoptera: pyralidae) infestation census from oil palm plantation on peat soil in Sarawak - Zulkefli Masijan,; Norman Kamarudin,; Ramle Moslim,; Alindra Gerald Sintik,; Siti Nurul Hidayah Ahmad,; Siti Ramlah Ahmad Ali, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Tirathaba rufivena is the major pest in oil palm plantation planted in peat soil in Sarawak. High infestation was reported in Miri, Mukah and Sibu. Censuses on the infestation of T. rufivena were conducted at three different locations, i.e. in Miri (young palm), Mukah (mature palm) and Sibu (ablation samples). Samples for census were taken from infested bunches, female and male inflorescences. The census was done by chopping the bunches and the female inflorescences while for the male inflorescences, the bottom of spikelets were cut to determine the number of live larvae and pupae. The census reveiled that in Sibu, a high infestation of T. rufivena was found on male inflorescences compared to bunches of female inflorescences. The mean number of live larvae found in male inflorescences for the first and second day of census recorded 35.3 ± 15.7 and 14.0 ± 7.3, respectively. The highest number of live larvae recorded from male inflorescences was 207 and 65, respectively. Meanwhile, the mean number of live larvae from infested bunches and female inflorescences on the first day were 9.9 ± 3.5 and 19.4 ± 4.4, respectively. On the second day of census, the mean number of live larvae recorded on bunches and female inflorescences were 4.8 ± 1.5 and 12.7 ± 2.8, respectively. Census on infested area in Miri from three different stages of female inflorescence and bunches recorded 8.0 ± 1.9 and 4.8 ± 0.6 highest number of live larvae. Post anthesis female inflorescences recorded the highest mean number of live larvae compared to pre anthesis and anthesising female inflorescences. Population study at Mukah on highly infested area recorded 60 live larvae from young bunches and 50 live larvae from matured female inflorescences. Based on the samples, bunch moth larvae or pupae were absent in 10% of infested female inflorescences and 11.7% of infested bunches (males and females inflorescences).